Shoulder Dystocia in Labor and Delivery: Interprofessional Team Response - Angela Blood; Barbara Scavone; Maryam Siddiqui; Kenneth Nunes (Association of American Medical Colleges, 2015)
Abstract Shoulder dystocia is an obstetric emergency that requires a coordinated team response. Because it does not occur frequently, it is challenging for providers to gain practical experience and expertise relying solely on clinical exposure. As there is no reliable way to predict shoulder dystocia, efforts must be aimed at timely interventions when it presents, to affect a quick delivery of the body and thus decrease the rate at which adverse outcomes occur. We present here in detail a simulation scenario for response to shoulder dystocia which delineates the roles not only of obstetric providers and nurses, but also of anesthesiology providers, surgical scrub technicians, and unit secretarial clerks. Other practitioners can incorporate this simulation training into their interprofessional educational programs. The educational materials include a simulation scenario with supporting documents, including a list of supplies and debriefing guide, a computer-based training online didactic, checklists of expected actions as defined by role, and two training videos. Shoulder dystocia is an unpredictable but serious obstetric emergency. As there is no reliable way to predict when a shoulder dystocia will occur, clinicians have limited ability to practice and optimize responses. Experts therefore recommend the adoption of shoulder dystocia management algorithms and interprofessional team practice drills to encourage a quick, coordinated response to shoulder dystocia episodes.